Systematic Literature Review of Sustainable Assessment Model in Vocational Higher Education - Suryani, Suryani; Umar Daihani, Dadan; Gustina Amran, Tiena Gustina Amran; Septiani, Winnie (Spektrum Industri, 2025)
Indonesia prioritizes vocational education to achieve the Golden Indonesia 2045 vision by producing competent, work ready graduates. Despite strategic policies, vocational enrollment remains low relative to academic pathways, and sustainability focused assessment model for vocational higher education are scarce. Therefore, this study aims to map and critically analyze existing sustainability assessment model for vocational higher education using a PRISMA based Systematic Literature Review and bibliometric analysis with VOSviewer. A total of 8,035 records (2018–2024) were retrieved, and the 20 articles that met the inclusion criteria were analyzed for thematic coverage, methodological approach, and integration of sustainability dimensions. The results showed that although many assessment model integrate economic, social, and environmental dimensions partially, few comprehensively addressed work readiness, sustainability literacy, and socio environmental impacts in vocational contexts. Bibliometric mapping further shows a dominance of general higher education studies and an underrepresentation of vocational-specific investigation. This study proposed a contextualized conceptual framework consistent with the Triple Bottom Line (economic, social, environmental) and selected SDG targets characterized by vocational competencies and institutional assessment practices. The framework offers guidance for policymakers and vocational institutions to design assessment systems that improve graduate relevance and institutional sustainability. The study contributes a systematic scientific map and a foundation for empirical testing of the proposed model.